Gestão pública, democracia e participação: um estudo de caso sobre a efetividade participativa dos conselhos de saúde dos municípios da 7ª coordenadoria regional de saúde do estado do ceará - Silva, Carlúcio Germano da (Universidade Federal Rural do Semi-Árido, 2019)
The public-democracy-participation-management relationship is a subject surrounded by controversy, and today, considering the Brazilian political-administrative framework, it remains a subject of important discussion. In this context, the present work seeks to evaluate the participatory effectiveness of the Municipal Health Councils (CMS's) of the municipalities that compose the 7th Regional Health Coordination (CRES) of Ceará. This is in line with the legal and political framework inaugurated by the Federal Constitution of 1988, in the light of the theory of participatory inclusive democracy. In order to do so, it is based on an approach that brings together key categories of the legal areas and, ineluctably, the policy, putting structural and normative issues in parallel with the methodological proposal developed by of participation in 4 D's (Density, Diversity, Durability and Deliberative Capacity). It is tried to approach alternatives other than those that centralize in the categories like cooptation and elites the main element to be considered to propose a quali-quanti immersion on the decision-making process in the scope of these collegiate. In the field of results, there is a series of structural failures and non-compliance with democratic norms and principles, to the detriment of effective participation in these Councils. As a result, the research hypothesis was confirmed, according to which the analyzed CMS function essentially as a chancellor of acts and policies aprioristically stitched by the municipal executive, as a consequence of the lack of resources, of a weak vocalization, of the protagonism of third parties who are not members of these participatory forums and the sedimentation of an imbalance in the power sharing objectified by the constituent legislator when instituting participatory management of Brazilian public health
Keywords: Conselhos de saúde; Participação; Efetividade; Health councils; Participation; Effectiveness; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA